Low power gas sensor array on flexible acetate substrate. (13th June 2017) - Benedict, Samatha; Basu, Palash Kumar; Bhat, Navakanta
Abstract: In this paper, we present a novel approach of fabricating a low-cost and low power gas sensor array on flexible acetate sheets for sensing CO, SO2, H2 and NO2 gases. The array has four sensor elements with an integrated microheater which can be individually controlled enabling the monitoring of four gases. The thermal properties of the microheater characterized by IR imaging are presented. The microheater with an active area of 15 µ m × 5 µ m reaches a temperature of 300 °C, consuming 2 mW power, the lowest reported on flexible substrates. A sensing electrode is patterned on top of the microheater, and a nanogap (100 nm) is created by an electromigration process. This nanogap is bridged by four sensing materials doped with platinum, deposited using a solution dispensing technique. The sensing material characterization is completed using energy dispersive x-ray analysis. The sensing characteristics of ZnO for CO, V2 O5 for SO2, SnO2 for H2 and WO3 for NO2 gases are studied at different microheater voltages. The sensing characteristics of ZnO at different bending angles is also studied, which shows that the microheater and the sensing material are intact without any breaking upto a bending angle of 20°. The ZnO CO sensor shows sensitivity of 146.2% at 1 ppm with good selectivity.